Integrasi Pendekatan Etnosains dalam Pembelajaran Sains untuk Meningkatkan Keterampilan Berpikir Kritis Siswa - Fitria Hidayati; Julianto Julianto (DIDAKTIKA, 2025)
This study aims to explore the integration of ethnoscience approaches in science learning to improve students' critical thinking skills. This research was carried out with a qualitative approach with this type of research, namely descriptive analysis, while the data collection technique in this study is a document study or literature study in research that has been carried out previously. Research shows that students who use this approach have higher motivation compared to those who use conventional learning methods. The results of the literature show several main findings related to the ethnoscience approach, including the positive influence of the ethnoscience approach on various aspects, including the improvement of students' critical thinking skills. This study shows that the ethnoscience approach improves students' critical thinking skills.